Taxonomy of the telenomus busseolae species-complex (Hymenoptera: Scelionidae) egg parasitoids of cereal stem borers (Lepidoptera: Noctuidae, pyralidae) - Polaszek, A.; Ubeku, J.A.; Bosque-Perez, N.A. (1993)
Morphological studies of different populations of what was previously considered to be a single species, Telenomus busseolae Gahan, revealed a complex of three distinct species. A total of four species were found to belong to this complex, all of which are egg parasitoids of stem boring Lepidoptera belonging to the closely related noctuid genera Busseola and Sesamia, with a single record from the pyralid stem borer genus Coniesta. All these host genera are of major economic importance as cereal pests. Two of the four Telenomus spp. are fully sympatric with regard to distribution, hosts and oviposition period. Two species, Telenomus isis and Telenomus nagarajae, are described as new.